The ameliorative effects of choline on ethanol-induced cell death in the neural tube of susceptible BXD strains of mice - Xu, Fannia; Thomas, Jennifer D.; Goldowitz, Dan; Hamre, Kristin M. (Frontiers in Neuroscience, 2023)
Introduction Fetal alcohol spectrum disorders (FASD) are the leading preventable cause of intellectual disability, providing the impetus for evaluating various potential treatments to ameliorate ethanol’s teratogenic effects, particularly in the nervous system. One treatment is the dietary supplement choline which has been shown to mitigate at least some of ethanol’s teratogenic effects. The present study was designed to investigate the effects of genetics on choline’s efficacy in ameliorating cell death in the developing neural tube. Previously, we examined BXD recombinant inbred mice, and their parental C57BL/6 J (B6) and DBA/2 J strains, and identified strains that were sensitive to ethanol’s teratogenic actions. Thus, we used these strains to identify response to choline treatment. Materials and methods Timed pregnant mice from 4 strains (B6, BXD51, BXD73, BXD2) were given either ethanol or isocaloric maltose-dextrin (5.8 g/kg in two administrations separated by 2 h) with choline at one of 3 doses: 0, 100 or 250 mg/kg. Subjects were exposed via intragastric gavage on embryonic day 9 and embryos were collected 7 h after the initial ethanol administrations. Cell death was analyzed using TUNEL staining in the developing forebrain and brainstem. Results Choline ameliorated the ethanol-induced cell death across all 4 strains without causing enhanced cell death in control mice. Choline was effective in both the developing telencephalon and in the brainstem. Both doses diminished cell death, with some differences across strains and brain regions, although the 100 mg/kg dose was most consistent in mitigating ethanol-related cell death. Comparisons across strains showed that there was an effect of strain, particularly in the forebrain at the higher dose. Discussion These results show that choline is effective in ameliorating ethanol-induced cell death at this early stage of nervous system development. However, there were some strain differences in its efficacy, especially at the high dose, providing further evidence of the importance of genetics in influencing the ability of choline to protect against prenatal alcohol exposure.